THE MAIN TRENDS IN THE ACTIVITY OF AGRI-FOOD COOPERATIVES IN ALMERÍA, SPAIN - Irina-Adriana CHIURCIU; Elena SOARE; Ionela-Mituko VLAD; Elena TOMA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Located in the South-East of Spain, the province of Almería was considered in the first part of the twentieth century, a poor region. Despite the infertile soil, the limited resources of water and the land not exactly suitable for agriculture, today over 70% of the vegetables exported from Spain are produced here. In the largest greenhouse in the world, as Almería is also called nowadays, are grown tomatoes, peppers, cucumbers, eggplants, with a high yield and a low level of pesticides. The practice of intensive agriculture has led to the growth of the economy of the area, which is mainly based on agriculture and tourism. This paper focuses, especially, on the analysis of relevant indicators for the specific activity of the agri-food cooperatives in Almería. In order to highlight the impact of the economic activity of Almería’s cooperatives on the economy, the paper presents a series of indicators of horticultural production in Spain. The statistical data presented and analysed that formed the basis of this paper were provided by Eurostat, Cooperativas Agro-alimentarias de España Grupo Cooperativo Cajamar.